Psychosocial Aspect in the Acceptance of COVID-19 Vaccines (Systematic Review) (Jurnal Ilmu Kesehatan Masyarakat, 2021)
COVID-19 vaccine can protect the public and suppress COVID-19 cases. But there are still many people who refuse to be vaccinated. The study aims to analyze the psychosocial aspects in the Acceptance of COVID-19 Vaccines. This study is a systematic review with PRISMA (Preferred Reporting Items for Systematic Reviews & Meta-Analyses). The database used to search data and information is PubMed. The keywords used during the search process are "Determinants" OR "Accepting" AND "Acceptance of COVID-19 Vaccination". The most psychosocial aspects related to COVID-19 vaccine acceptance include education level, income level, race, type of work, trust in the existence of COVID-19, trust in COVID-19 information resources, trust in medical and health workers, and having family members or friends who are infected with COVID-19. Education level, income level, and race influence the most in accepting the COVID-19 vaccine. The COVID-19 vaccine program should consider and overcome the challenges of receiving and rejecting vaccines from the public by looking at these aspects.